PSX-B-17 Effects of Enzymatic and Microbial Supplements on Shedding of E. Coli and Salmonella During the pre-Harvest Finishing Period in Growing Lambs. (21st September 2022) - Krueger, Lucas A; Hafla, Aimee; Spangler, David
Abstract: Effects of enzymatic and microbial feed supplements on fecal pathogen shedding were tested in a 2×2 factorial, randomized complete block design, where the experimental unit (n = 20) was a pen of 3 lambs. Lambs were blocked (i =10) by weight and then randomly assigned within block to phase 1 treatments of control (C) or a feed enzyme product (E). Upon acclimation to diet, pens were treated daily in feed as E (1.1 g per animal of Maximiser-Ex; Agri-King, Inc.), or control (C) for 76 days. After phase 1, pens were randomly assigned into phase 2 within block to new treatments comprised of control (C) or a direct fed microbial product (DFM; Tri-Lution; Agri-King, Inc.). Phase 2 treatments were supplemented daily at 16 g per animal for 16 d. After 2 d, lambs were gavaged with 10^8 CFU of a non-shiga-toxin-producing, novobicin-resistant and tellurite-resistant E. coli O157:H7 (ATCC 43888). Stool samples were collected prior to gavage and on d 1, 2, 7, 9, and 14 after gavage. Samples were pooled within pen and analyzed for E. coli O157:H7 on selective media with novobicin and tellurite, total Salmonella, and total coliform bacteria. Data were analyzed by ANOVA and means were separated by Tukey HSD test. Pens supplemented with E during phase 1 demonstrated significantly decreased (P < 0.05) total coliform bacteria in stool enumerated prior to gavage. E. coli O157:H7 was decreased significantly (P < 0.01) by main effect of DFM treatment. Logarithmic differences between DFM and C treatments were >4.0 on d 2 post-gavage and persisted significantly through d 14. Shedding of Salmonella CFU was not affected. Findings demonstrate that enzymatic and microbial treatments decreased shedding of pathogenic bacteria in stool.